(untitled) (Research, Society and Development, 2025)
Introduction: Menopause, marked by the cessation of menstruation, often brings vasomotor symptoms, sleep disturbances, and urogenital changes, impacting quality of life. Hormone therapy (HT), combining estrogen and progesterone, alleviates symptoms and prevents long-term complications. Methods: A narrative literature review was conducted using PubMed, Scielo, and Google Scholar, focusing on studies published between 2020–2024 in English or Portuguese. Inclusion criteria targeted studies on combined hormone therapy (CHT) for menopause, excluding those on other treatments, small sample sizes, or low-quality evidence. Results and Discussion: CHT effectively reduces vasomotor symptoms, enhances sleep quality, and improves urogenital health while protecting bone density. Initiating HT within 10 years post-menopause reduces cardiovascular risks, as evidenced by studies like Baik et al. (2024) and Gu et al. (2024). Transdermal or vaginal routes minimize thrombotic risks compared to oral formulations. However, CHT poses risks, such as increased breast cancer and thromboembolism, necessitating personalized approaches. Conclusion: CHT offers significant benefits for menopausal symptom management and bone and cardiovascular health. Timing, dosage, and administration route are key to optimizing safety and efficacy. Individualized treatment, based on rigorous monitoring, ensures improved quality of life for women experiencing menopause.